Identification of Risk Areas of Malnutrition among School Children (0-14 years) in Gujars Community of Great Kashmir Himalayas - G.M. Rather , (National Geographical Journal of India, 2022)
The present research work was carried out on identification of risk areas of malnutrition among schoolchildren (0-14 years) in Gujjars Community of Great Kashmir Himalayas. Nutrition intake was examinedin comparison to ICMR recommended dietary allowances (RDA). The weight of all sample children wasmeasured and compared with ICMR (Indian Council for MedicalResearch) standard and then categorisedinto different nutritional grades. Data regarding prevalence of nutrition deficiency diseases was alsoobtained during field survey. Composite Index method was employed for categorisation of samplevillages in risk areas. The investigation reveals that variation in the availability of nutrients in the diet hasbadly affected the health of school children and leads to malnutrition. Grades of malnutrition varies withaltitude and majority of sample villages of higher altitudinal zones of E and F were areas of I and IIcategory of risk and thus are areas of very high and high priority. Suggestions have been made forimprovement of nutrition status of children from 0-14 age group in the risk areas.